Railway vehicle modelling for the vehicle–track interaction compatibility analysis. (September 2016) - Magalhães, H; Ambrósio, J; Pombo, J
Railway vehicle homologation with respect to running dynamics is addressed via dedicated norms that require the knowledge of the accelerations and wheel–rail contact forces obtained from experimental computational testing. Multibody dynamics allows the modelling of railway vehicles and their simulation on realistic operations conditions. However, the representativeness of the multibody models, and the results of their use in railway dynamics are greatly influenced by the modelling assumptions and their ability to represent the operational conditions. In this paper, two alternative multibody models of a railway vehicle are presented and simulated in a realistic railway track scenarios to appraise the consequences of different modelling assumptions on the railway dynamic analysis outcome. A vehicle–track interaction compatibility analysis is performed afterwards according to norm EN 14363. The analysis consists of two stages: the use of a simplified method, described in the norm for the identification of the different performance indexes from the railway vehicle dynamic analysis outcome; and the visual inspection of the vehicle motion with respect to the track via dedicated visualization tools. The results of the virtual vehicle homologation tests are presented and discussed in face of the modelling assumptions used, being significant differences identified between the railway vehicle modelled with cylindrical joints with clearances or with equivalent force elements. It is also concluded that the use of clearance joints prevents the need to use modelling assumptions on the equivalent force elements that have limited or no physical meaning, thus reducing the number of modelling parameters for which a high level of abstraction has to be exercised.